Investigating the Success of Academically Talented Students with Financial Need: Pathways and Decisions of Jack Kent Cooke Scholars - Brandon, Laurel E.; Reis, Sally M.; McCoach, D. Betsy (International Journal for Talent Development and Creativity, 2021)
This study investigated the outcomes of financial aid, advising support, and other enrichment opportunities provided to academically talented high school and college students who have strong financial need. The Jack Kent Cooke Foundation provides funding to exceptionally promising young scholars from low-income families to enable them to attend and graduate from competitive universities and also complete graduate school. This research identified positive outcomes of this support for academically talented scholars who received financial support. All responding scholars attended and graduated from selective, competitive colleges, completing their undergraduate education at a much higher rate than their socioeconomic peers and the general population. Over half of the scholars also were enrolled in or completed graduate school.